University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 9 - Section 9.10 - The Binomial Series and Applications of Taylor Series - Practice Exercises - Page 553: 59


$\Sigma_{n=0}^\infty \dfrac{(-1)^n (\pi)^{2n+1} (x)^{2n+1}}{(2n+1)!}$

Work Step by Step

Since, we know that the Taylor Series for $\sin x$ is defined as: $ \sin x=\Sigma_{n=0}^\infty \dfrac{(-1)^n x^{2n+1}}{(2n+1)!}=x-\dfrac{x^3}{3!}+\dfrac{x^5}{5!}-\dfrac{x^7}{7!}+...$ Now, $ \sin (\pi x)=\Sigma_{n=0}^\infty \dfrac{(-1)^n (\pi x)^{2n+1}}{(2n+1)!}=(\pi x)-\dfrac{(\pi x)^3}{3!}+\dfrac{(\pi x)^5}{5!}-\dfrac{(\pi x)^7}{7!}+...$ or, $=\Sigma_{n=0}^\infty \dfrac{(-1)^n (\pi)^{2n+1} (x)^{2n+1}}{(2n+1)!}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.